Exploring reactions of amines-model compounds with NH2: In relevance to nitrogen conversion chemistry in biomass. (1st May 2021) - Rawadieh, Saleh E.; Altarawneh, Mohammednoor; Altarawneh, Ibrahem S.; Shiroudi, Abolfazl; El-Nahas, Ahmed M.
Graphical abstract: Highlights: Kinetics parameters for H abstractions by NH2 from model N-species are presented. Abstraction from α C–H requires lower activation energies than other sites. Updating kinetic models herein achieve some improvements in the yields of NH2 /NH3 . For heterocyclic-NH, the rate constants follow the order carbazole > indole > pyrrole. Abstract: Amine-containing compounds (primary/NH2, secondary/NH and heterocyclic –NH) -are principal nitrogenated species in biomass. Amine radical (NH2 ) emerge as an important intermediate in the initial stages of biomass combustion and pyrolysis. A detail understanding of the nitrogen conversion chemistry necessitates acquiring accurate reaction rate constants for reactions of NH2 radicals with amine-bearing molecules. With the absence of relevant kinetic parameters, pertinent kinetic model on oxidation of surrogate biomass compounds often utilize values extracted from analogous reactions with OH and CH3 radicals. Herein, we report comprehensive kinetic parameters for H abstraction by NH2 radicals from various C/H sites in seventeen amine model compounds, comprising primary/secondary alkyl and aromatic amines. Fitted activation energies were found to linearly correlate with N–H bond dissociation enthalpies via Evans–Polanyi plots. In primary C2 -C4 alkylamines and in diethylamine, abstraction from the α C–H site (gem to the amine group) largely dominates that from the NH2 group. Abstraction from NH and methyl sites in dimethylamine entails comparable importance. A vinylic CH2 group does not alter kinetics of abstraction for unsaturated amines when contrasted with primary amines. Reaction rate constants for H abstraction from heterocyclic-NH structures follow the order carbazole > indole > pyrrole, reflecting corresponding BDHs values for their N–H bonds. Updating kinetic models on combustion of small amines structures, with the newly calculated reaction rate constants, slightly improves their predictive performance toward the yields of NH2 /NH3 .